2013
DOI: 10.1007/s11743-012-1428-y
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Polyglucosides as Components of Water Based Lubricants

Abstract: Water can be used as an ecological lubricant base if it is possible to select additives which can beneficially modify its tribological and corrosion properties. Additionally, those additives should not be harmful to human health and the natural environment. These conditions limit or even eliminate the possibility for the application of the additives used in traditional oil bases as they are insoluble in water and often toxic. Alkyl polyglucosides (APGs) have been suggested as additives improving lubricating pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…They act as liquid crystal reservoirs to improve hydration and form elastic networks with water. Hence overall stability of their formulations and long-term maintenance of skin moisture is achieved [20] .…”
Section: Resultsmentioning
confidence: 99%
“…They act as liquid crystal reservoirs to improve hydration and form elastic networks with water. Hence overall stability of their formulations and long-term maintenance of skin moisture is achieved [20] .…”
Section: Resultsmentioning
confidence: 99%
“…The friction coefficient behavior of AGPs was compared to Glucopon 600 CSUP. Sulek et al have studied the tribological property of Glucopon 600 CSUP and the effect of varying friction pairs [48,49]. They showed that it can effectively reduce motion resistance and wear, and a low friction below 0.1 is achieved after reaching the CMC (CMC = 0.05%).…”
Section: Discussionmentioning
confidence: 99%
“…The low movement resistance and high load-bearing capacity of such systems are the result of the adsorption of a protective layer with ordered structure, which is concluded as an adsorptive-structural mechanism [47]. In addition, they have used biodegradable multi-component solutions based on alkyl polyglycosides (APGs) as a component to reduce friction and wear [48,49]. APGs with a longer alkyl chain length (C12-14) have a high surface affinity and reduce motion resistance and wear more effectively, while APGs C8-C10 have better anti-seizure properties [49].…”
Section: Introductionmentioning
confidence: 99%
“…APG with DP from 1 to 5 containing alkyl chains from 6 to 14 carbons are soluble in water, such as C8/C10 polyglucosides, C9-11 polyglucosides, and C12/C14 polyglucosides, they are considered as water solubility; but these molecules with 16-22 carbon atoms are oil-soluble. Their water solubility increases with increasing DP (Sułek, Ogorzałek, Wasilewski, & Klimaszewska, 2013). Of course, cloud point can also be used to evaluate water solubility to some extent (von Rybinski & Hill, 1998).…”
Section: Hlb Number and Solubilitymentioning
confidence: 99%